2016
DOI: 10.1177/0748233716658579
|View full text |Cite
|
Sign up to set email alerts
|

Histologic study of testis injury after bisphenol A exposure in mice

Abstract: The health effects of bisphenol A (BPA) have become a great concern in recent years. In this study, the reproductive toxicity of BPA was investigated. Male CD-1 mice were orally administrated with BPA (0, 100, 300 and 600 mg kg body weight) for 56 consecutive days. Results showed that relative testis weight to total body weight was significantly lower in the high-dose group ( p < 0.01, p < 0.05). Microscopic examination under light and transmission electron microscopes showed disorders of spermatogenesis after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
1
27
3
Order By: Relevance
“…It is reported that a decrease in the level testosterone in BPA-treated rats led to atrophy of seminiferous tubules, degeneration of cells, and complete absence of spermatogenesis [21] . Also, the impairment of the basal lamina of seminiferous tubules and damaged tight junctions between sertoli cells could be attributed to BPA-induced cell injury as reported by [22] . Additionally, the intercellular spaces represent progressive degenerative changes affecting cell membrane integrity secondary to oxidative stress induced by BPA.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is reported that a decrease in the level testosterone in BPA-treated rats led to atrophy of seminiferous tubules, degeneration of cells, and complete absence of spermatogenesis [21] . Also, the impairment of the basal lamina of seminiferous tubules and damaged tight junctions between sertoli cells could be attributed to BPA-induced cell injury as reported by [22] . Additionally, the intercellular spaces represent progressive degenerative changes affecting cell membrane integrity secondary to oxidative stress induced by BPA.…”
Section: Discussionmentioning
confidence: 70%
“…BPA may act via several different mechanisms involving interaction with estrogen receptors and/or by production of a minor but potent estrogenic metabolite [30] . A decrease in the level of androgen binding protein could be the possible mechanism for the reproductive toxicity of BPA [22] . Others reported that a low BPA concentration can induce spermatogenesis disorders mainly through decreasing androgen receptor expression [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Small fragments (1 mm 3 ) of dissected testes were removed and fixed in 2.5% glutaraldehyde in 0.1 M phosphate buffer (pH 7.4), post-fixed in 1% OsO 4 . The following protocol referred to the standard procedures (Tian et al, 2017). The ultrastructural features of testicular sections were examined under a transmission electron microscope (TEM) (Hitachi, HT7700, Japan).…”
Section: Ultrastructure Analysis Of Testesmentioning
confidence: 99%
“…Numerous studies in animal models have reported the deleterious effects of exposure to bisphenols. Tian et al found that male CD-1 mice exposed to BPA had decreased testis weight, damage to basal lamina of seminiferous tubules and tight junctions between Sertoli cells, and decreased levels of the androgen-binding protein [61]. BPA exposure of pregnant CD-1 mice results in altering the tissue organization of ovaries and mammary glands, and alters the estrous cycle in adulthood via modulation of their morphogenesis specific genes' expression [62].…”
Section: Endocrine Disruption and Reproductive Abnormalitiesmentioning
confidence: 99%